A case of specific pemphigus vulgaris in the oral cavity - HORI, Shinsuke; OKUBO, Yasunori; IIZUKA, Tadahiko; BESSHO, Kazuhisa (Japanese Journal of Oral and Maxillofacial Surgery, 1994)
Autoimmune bullous dermatosis is classified into 6 distinct entities based on clinical symptoms and findings obtained from recent advances in immunoelectron microscopic techniques. The 6 entities are: 1) the pemphigus group, 2) dermatitis herpetiformis, 3) linear IgA bullous dermatosis, 4) the pemphigoid group, 5) epidermolysis bullosa acquisita, and 6) herpes gestationis. We report a specific pemphigus vulgaris patient with clinical pathohistological features of bullous dermatosis who showed immunohistological characteristics of pemphigus vulgaris and bullous pemphigoid.